Planted forests : uses, impacts, and sustainability - Evans, Julian, 1946- (Published jointly by Food and Agriculture Organization of the United Nations and Cabi Pub., 2009)
This book contains nine chapters providing a synthesis of the multiple uses, impacts and sustainability of planted forests by looking at the past, outlining the present situation and highlights the outlook and issues for the future. In addition, the policy, institutional and ownership issues in planted forests are also covered.